ANALISIS STRATEGI GURU DALAM MENANAKAN KARAKTER DISIPLIN PADA SISWA KELAS RENDAH DI UPT SPF SD NEGERI TABARINGAN 5 KOTA MAKASSAR - nensi, nensi; Hastati, Sri; Fitri, Riskal (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2023)
The purpose of this study was to find out: 1) to find out the teacher's strategy in instilling the character of discipline in low-grade students at UPT SPF SD Negeri Tabarringan 5 Makassar City, 2) to find out what are the supporting and inhibitory factors in instilling the character of discipline in low-grade students at UPT SPF SD Negeri Tabarringan 5 Makassar City. This research was conducted using descriptive qualitative research methods, data collection was carried out by observation questionnaire interviews and documentation techniques while the data analysis was carried out in three stages, namely, data reduction, data presentation and drawing conclusions. Based on the results of the research that has been done, it was found that the strategy used by the teacher in instilling the character of discipline in low-grade students at UPT SPF SD Negeri Tabaringan 5 Makassar City is through several elements, namely rules of procedure, habituation, exemplary, punishment and rewards. The supporting factors are parents' active war, teacher supervision, and self-awareness, while the inhibiting factors are parents